Sialyltransferases and Neuraminidases: Potential Targets for Cancer Treatment - Sagorika Nag; Abhimanyu Mandal; Aryaman Joshi; Neeraj Jain; Ravi Shanker Srivastava; Sanjay Singh; Arun Khattri (Diseases, 2022)
Cancers are the leading cause of death, causing around 10 million deaths annually by 2020. The most common cancers are those affecting the breast, lungs, colon, and rectum. However, it has been noted that cancer metastasis is more lethal than just cancer incidence and accounts for more than 90% of cancer deaths. Thus, early detection and prevention of cancer metastasis have the capability to save millions of lives. Finding novel biomarkers and targets for screening, determination of prognosis, targeted therapies, etc., are ways of doing so. In this review, we propose various sialyltransferases and neuraminidases as potential therapeutic targets for the treatment of the most common cancers, along with a few rare ones, on the basis of existing experimental and in silico data. This compilation of available cancer studies aiming at sialyltransferases and neuraminidases will serve as a guide for scientists and researchers working on possible targets for various cancers and will also provide data about the existing drugs which inhibit the action of these enzymes.